Analisa Reliability dan Availability Mesin Screw Press Kelapa (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
The performance of a machine for the production process depends on the reliability and availability of the machine. At PT. Ujong Neubok Dalam (UND) is a company that produces Crude Palm Oil (CPO) and kernels. The production target in the company is 270 tons/day of Fresh Fruit Bunches (FFB) which will be produced into CPO. Problems that often occur at PT. UND is related to machine breakdown (Down Time). The implication is that the ongoing production process is not optimal. This study aims to determine the level of availability and reliability of the screww press machine. The focus of the study is placed on the screww press machine station because after the initial observation the frequency of machine downtime often occurs in screw press machines. The failure of the screw press machine components can hamper the production process, resulting in not achieving the production targets set by the company. In this study, we have analyzed the level of reliability and availability of the oil palm screw press machine. From the calculation results, we can see that the level of reliability of the screw press machine 2-3 has a reliability level of 90% with an operating time of 5 days, and the level of reliability of the screw press machine will decrease with increasing time and for the availability of components for a period of 30 days.